The Value of Landscape Restoration in Uzbekistan to Reduce Sand and Dust Storms from the Aral Seabed - Akramkhanov, A. (World Bank, Washington, DC, 2021)
Central Asia experiences frequent sand and dust storms (SDS), which have been made worse by human activity. The main objective of this study is to provide an economic analysis of the benefits of afforestation of the former Aral Seabed in Uzbekistan. The objective of this study is to estimate economic benefits attributed to afforestation of the former Aral Seabed in Uzbekistan. Proper estimation and categorization of economic benefits associated with each scenario of landscape restoration enables the Government of Uzbekistan and local authorities to allocate limited resources in an efficient way, supporting promising rehabilitation techniques and practices. Based on wind erosion modeling results, this study measures soil retention ecosystem services in the former Aral Seabed in Uzbekistan. To understand the value of soil retention ecosystem services, several scenarios of landscape restoration are considered.